Pelatihan Perbanyakan Tanaman Hias Dengan Metode Tunggul dan Tak Dinodai Bagi Kelompok Perempuan PKK - Catalina Aurora Rose (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
As more and more people are doing activities at home due to the COVID-19 pandemic, members of the Mandal PKK group are encouraged to care for various types of local and imported ornamental plants. There are many types of "tuber" or "tuber stem" ornamental plants that are very popular and have very high economic value, such as Alocasia sp and Aglonema sp. This training aims to provide technical knowledge to the public regarding the propagation of borer pests using soilless media. This training was carried out with the approval of the District Pankep COVID-19 Task Force. After training, group members are supported in replanting propagation, especially transplanting plants into new pots and proper plant care. If each member who is given at least 5 beetles can grow, graft, and care for at least 4 or even 5 beetles on ornamental plants, the average success rate is above 80%. Training on cultivating bulbs and heads of ornamental plants using a hoe system and soilless methods can provide knowledge to local communities and is expected to continue in the future.